Implementasi Aplikasi Sijapti Pada Seleksi Terbuka Jabatan Pimpinan Tinggi Pratama Dilingkungan Pemprov Banten - ilham priyooambudi (HK Publishing, 2025)
Employee is the main factor among other factors that influence the development of government in a region. Based on this, the author is interested in conducting research with the title The Role of Regional Personnel Agencies in Implementing the High Leadership Position Information System Application (SIJAPTI) in the Open Selection for Primary High Leadership Positions within the Banten Provincial Government. This research design is qualitative research with descriptive methods and an inductive approach. Data collection techniques were carried out using interviews, observation and document review. The selection of informants used purposive and snowball sampling methods. This is influenced by inhibiting factors, such as leadership policies and a lack of technological understanding among potential selection participants. The supporting factors in implementing this program are having a strong legal basis, budget availability, and commitment from the regional government. In addition, the Regional Civil Service Agency has made several efforts to implement the SIJAPTI application in the implementation of the Open Selection of High-Level Pratama Leadership Positions, including completing the simplification of the organizational structure, coordination and consultation with central agencies, and preparing budget allocations.